O uso de roteiros de aprendizagem para o desenvolvimento da autonomia dos estudantes em uma escola municipal da prefeitura de Vitória - Abreu, Geórgia Papi de (2023)
As a main objective, this study proposed to analyze how the Learning Guides (RA) used at the municipal school Edna de Mattos Siqueira Gáudio (Emef EMSG), located in Vitória/ES, contribute to the students' autonomy. The school's pedagogical approach was one of the motivations for the research, as it has attempted to experience a progressive education, emphasizing the following concepts: autonomy, solidarity and cooperation. The selected school is also the place where the author of this research works. The research is based theoretically on studies about autonomy, especially on those that dialogue with these concepts from a critical perspective, aiming at systematizing the teaching methodology through Learning Guides, developed at the school. Based on Paulo Freire studies, the aim was to specifically identify the educators’ conception of autonomy and their perceptions of autonomy when applying the Learning Guides. Using a qualitative research method, the study intended to analyze the Pedagogical Political Project (PPP), the schools Learning Guides and the educators; answers to a questionnaire applied during an inset day. To make this data, a group of 20 educators answered a Google Form questionnaire. Most educators consider the Learning Guides as a valuable tool for organizing and directing teaching, to develop student autonomy, especially regarding the organization of content; encouragement of research and reading; initiative, engagement and protagonism, yet highlighting aspects relevant to the learning of both students and educators, considering the close relationship between teaching and learning underlined by Paulo Freire. From this perspective, we highlight the educators' perceptions on the need to search for well-structured pedagogical planning, prior organization, flexibility for adjustments and adaptations throughout the educational process, which characterizes the critical reflection proposed by Freire. Doing and thinking about doing is opposed to the mechanical or spontaneous situations that some educators referred to. The results also reveal that planning Learning Guides can be complex and require attention to several aspects, including available time, collaboration between educators, adaptation to students and the search for innovation. Overcoming these difficulties requires effort, dedication, and collaborative work, but the benefits in terms of student autonomy can make the investment of time and energy worthwhile. From the results, we created a guide containing a proposal of pedagogical mediation for the Learning Guide as a capstone project to be shared with educators who work for the municipal government in Vitória.